2016
DOI: 10.5762/kais.2016.17.6.233
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of static balance abilities measure using a smartphone's acceleration sensor

Abstract: The purpose of this study is to investigate the reliability of static balance measurements using a smartphone.Thirty subjects were selected among university students who had no fractures, history of operation, or inflammatory arthritis, and they had not started regular exercise during the past three months. The smartphone used in this study was a Galaxy S5LTE (SM-G900F, Samsung, Korea, 2014), and the application was a Sensor Kinetics Pro (Ver. 2.1.2, INNOVENTIONS Inc., US, 2015). Static balance ability was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Second, this study found that it has a higher validity when measuring balance abilities with the gyroscope sensor than with the acceleration sensor. It shows similar results to the studies of De Groote et al [20] and Han Seul-gi et al [29] that there was negligible correlation when performing balance tasks with low difficulty level, and that there was a fair or higher correlation when performing balance tasks with higher difficulty level. O'Sullivan et al [30] reported that acceleration data can be measured in more difficult balance tasks, which supports this study.…”
Section: Discussionsupporting
confidence: 88%
“…Second, this study found that it has a higher validity when measuring balance abilities with the gyroscope sensor than with the acceleration sensor. It shows similar results to the studies of De Groote et al [20] and Han Seul-gi et al [29] that there was negligible correlation when performing balance tasks with low difficulty level, and that there was a fair or higher correlation when performing balance tasks with higher difficulty level. O'Sullivan et al [30] reported that acceleration data can be measured in more difficult balance tasks, which supports this study.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, the measurement of shoulder range of motion using a smartphone was reported by Lim et al [ 19 ], and the measurement of heart rates using a smartphone was investigated by Matsumura and Yamakoshi [ 20 ]. In addition, the measurement of balance using a smartphone was investigated by Han et al [ 21 ]. However, the reliability and validity of smartphones to measure JPS of dorsi-plantar flexion of the ankle have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%